HARAPAN MAHASISWA PROGRAM STUDI ILMU PERPUSTAKAAN UNIVERSITAS PADJADJARAN MENJADI PUSTAKAWAN - Ekawati, Desi; Radiah, Saleha (Edulib, 2014)
AbstractThis research about â€œexpectation of library science student to be a librarianâ€ conducted on students Departement Library Science Padjadjaran University. The purpose of this research was to determine the extent of the correlation between student studied library science with expectation to be a librarian. This research used a survey method. The population in this research was student of library science class of 2009-2011 are totaled 231 people and obtained 70 samples. Data collection techniques use questionnaires, observations, interviews, and literature. The conclusion of this research is there is a certain correlation between student studied library science with expectations to be a librarian. This correlation is neutral. Students studied the library science, but do not know, dubious, or even no matter whether the future will be a librarian or not. Suggestion from this research is a name reconsideration of the profession and the motivation of the profession itself.Keywords: Expectation of library science student, Library Science, Librarian, survey methodAbstrakPenelitian untuk mengetahui hubungan mahasiswa mempelajari ilmu informasi dan perpustakaan dengan harapannya menjadi pustakawan. Menggunakan metode penelitian survey, populasinya mahasiswa Prodi Ilmu Perpustakaan Angkatan 2009-2011 berjumlah 231 orang dengan responden 70 orang. Teknik pengumpulan data menggunakan angket, observasi, wawancara dan studi pustaka. Hasil penelitian menunjukkan hubungan bersifat netral antara mahasiswa mempelajari ilmu informasi dan perpustakaan dengan harapan menjadi pustakawan. Mahasiswa mempelajari ilmu informasi dan perpustakaan namun tidak tahu, meragukan, atau bahkan tidak peduli apakah nantinya akan menjadi pustakawan atau tidak.Kata Kunci: Harapan mahasiswa, Ilmu Perpustakaan, Pustakawan, metode survei